Self-Concept and Emotional Intelligence in Relation with Digital Literacy - Alpian, Yayan; Sumantri, M. Syarif; Yufiarti, Yufiarti; Wulan Anggraeni, Sri (Journal of Nonformal Education, 2023)
As a student teacher candidate, the ability to communicate is a vital competency to be mastered. One of the best ways to share is how students and teacher candidates use technology. Advances in information and communication technology make digital literacy ability as significant as other abilities that exist in every individual human being. This study attempted to establish a link between self-concept and emotional intelligence and digital literacy abilities. This study uses the correlation method, with data collection carried out through a survey with an instrument in the form of a questionnaire for elementary school teacher education students at universities in West Java using the proportional random sampling technique. The results of this study indicate the correlation coefficient and the coefficient of determination, namely for self-concept with literacy ability, the correlation coefficient value is 0.563. This means a positive and significant relationship exists between self-concept and digital literacy ability, while emotional intelligence with digital literacy ability has a correlation coefficient of 0.651. This means a positive and meaningful relationship exists between emotional intelligence and digital literacy ability. The coefficient of determination of 0.433 means that the magnitude of the relationship between self-concept, emotional intelligence, and digital literacy ability is 43.3%. And the calculated F value is 103.730 from the Ftable value of 3.04. This research suggests that student-teacher candidates can develop self-concept and must be able to control emotional intelligence to improve digital literacy as a support in the learning process and to improve academic achievement